2015
DOI: 10.1159/000380849
|View full text |Cite
|
Sign up to set email alerts
|

Severe Generalized Weakness, Paralysis, and Aphasia following Administration of Irinotecan and Oxaliplatin during FOLFIRINOX Chemotherapy

Abstract: Background: Irinotecan is commonly used in combination with oxaliplatin as a component of FOLFIRINOX chemotherapy for several gastrointestinal malignancies. The purpose of this case report is to describe a patient who developed acute paralysis and aphasia while receiving her initial infusion of irinotecan. Case Report: A 67-year-old woman with newly diagnosed metastatic pancreatic adenocarcinoma presented for her first cycle of FOLFIRINOX chemotherapy. During her infusion of irinotecan, she developed acute ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…To date, 29 cases of transient dysarthria and/ or aphasia observed during or shortly following the administration of irinotecan have been reported in the literature and are summarized in Table 1 [12][13][14][15][16][17][18][19][20][21]27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 29 cases of transient dysarthria and/ or aphasia observed during or shortly following the administration of irinotecan have been reported in the literature and are summarized in Table 1 [12][13][14][15][16][17][18][19][20][21]27].…”
Section: Discussionmentioning
confidence: 99%
“…In all reported cases [12][13][14][15][16][17][18][19][20][21], clinical signs were stable and neurological examinations showed no evidence of neurological abnormalities, except dysarthria. Patients were monitored carefully and observed to return close to their baseline status within 1-2 h.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandar et al [22] reported a case of a 67-year-old woman with newly diagnosed metastatic pancreatic adenocarcinoma who was treated with FOLFIRINOX. During her first infusion of irinotecan, she developed acute onset of generalised weakness, paralysis of all extremities and nonfluent aphasia with a complete inability to communicate.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is commonly performed but rarely yields additional information. The measures described in the literature to alleviate this symptomatology are shown in Table 1 [8,9,11,[14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%